FROM CLIMATE TRANSPARENCY TO MARKET TRUST: A SYSTEMATIC REVIEW OF DISCLOSURE, VALUATION, AND REGULATORY DYNAMICS - Legendariah (ITB AAS Indonesia Surakarta, 2025)
Climate risk disclosure has emerged as a critical mechanism linking corporate transparency with market valuation, yet empirical evidence remains heterogeneous across contexts. This systematic literature review synthesizes 24 peer-reviewed articles (2015-2025) to examine how climate risk disclosure affects investor confidence and market valuation under varying regulatory dynamics. Following established systematic review protocols, studies were systematically sourced from four major databases (Scopus, ScienceDirect, Emerald Insight, Wiley) and analyzed using thematic synthesis. Results reveal that 68% of studies demonstrate positive relationships between disclosure quality and market outcomes, with high-quality climate disclosure associated with 15-25 basis points reduction in cost of capital and 3-8% increase in Tobin's Q. Investor confidence emerges as a critical mediator, accounting for approximately 60% of the total effect between disclosure and valuation. However, effectiveness is highly context-dependent: regulatory stringency, governance quality, external assurance, investor sophistication, and industry materiality act as decisive moderators. The study contributes the Climate-Trust-Value (CTV) Framework, integrating signaling, trust, and institutional theories to explain when, where, and how transparency translates into market value. Findings provide evidence-based guidance for corporate disclosure strategies, regulatory design, and investment decision-making in the evolving landscape of climate finance.